HISTORICAL ASPECTS OF FORMING PATRIOTIC IDEAS AS CIVIC VALUES IN PEDAGOGY SYSTEM OF HIGHER EDUCATION - N. I. Morozova; L. E. Galaganova (Вестник Кемеровского государственного университета, 2014)
The paper is devoted to forming patriotism as a civic value and to the tasks of Higher Education institutes.